Geochemical Insights into the Paleodepositional Environment of the Garagu Formation, Gara Anticline, Kurdistan, Northern Iraq - Mohialdeen, Ibrahim M.J.; Mirza, Tola A.; Abdalla, Shahra O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The Garagu Formation is mostly composed of carbonate layers with iron-rich horizons in the middle part. The geochemical evidence for the paleodepositional environment of the Garagu Formation in the Kurdistan Region of Iraq’s Gara anticline has been explored in this paper. A total of 9 samples from the Garagu Formation were analyzed by XRF for major elements and inductively coupled plasma–mass spectrometer for trace elements. From geochemical data of major and trace elements, including rare earth elements, a series of identification indexes, such as Sr/Ba, Rb/K2O, Th/U, U/Th, V/(V+Ni), δU, V/Sc, Sr/Cu, and C-Value ratios, are calculated, which can be used to indicate paleosalinity, ancient oxidizing environment, and paleoclimate conditions. As would be predicted in this limestone-dominated deposit, CaO has the greatest weight percentages of any sample. Several samples from the iron-rich mineralization in the middle part of the formation exhibit significant percentages of FeO. The elemental geochemical ratios indicate to saline shallow marine environment with lower salinity in the middle part of the formation. The paleoredox proxies revealed that the oxic to suboxic conditions prevailed during the deposition of the formation.